Overview of synoptic conditions over West Africa and North Atlantic before cyclogenesis - (:unkn) unknown (My University, 2010)
The objective of this study is to describe the large scale conditions over West Africa and the Atlantic Ocean before the occurrence of a cyclogenesis over the North Atlantic by comparing synoptic conditions of a 3 day average before the genesis days of all cyclones (269 cyclones given by the National Hurricane Center; NHC) with the mean Aug-Oct climatology from 1980 to 2004. Over West Africa, the mean synoptic pattern before cyclogenesis is characterized by the presence of a stronger monsoon layer and lower values of Outgoing Longwave Radiation than the climatology depicting the presence of deeper convection. Moreover, the potential of genesis is stronger before cyclogenesis over the West African coast than the climatology showing that strong low-level cyclonic vortices propagate from land to ocean in an atmosphere characterized by strong upper level support. Generally, before the occurrence of a cyclonic activity, the atmosphere is more unstable and African Easterly Waves are more active over West Africa than the climatology. Over the Atlantic Ocean, large scale conditions before cyclogenesis are characterized by the presence of high cyclogenesis contributors such as warmer waters, lower pressure, stronger mid-level humidity and higher degree of atmospheric instability.
Keywords: African Research